Cutaneous iontophoresis of vasoactive medications in patients with scleroderma‐associated pulmonary arterial hypertension. (17th November 2021) - Al Abdi, Sami; Almoushref, Allaa; Naal, Tawfeq; Melillo, Celia A.; Aulak, Kulwant S.; Ahmed, Mostafa K.; Chatterjee, Soumya; Highland, Kristin B.; Dweik, Raed A.; Tonelli, Adriano R.
Abstract: Background: It remains unknown whether the cutaneous microvascular responses are different between patients with scleroderma‐associated pulmonary arterial hypertension (SSc‐PAH) and SSc without pulmonary hypertension (PH). Methods: We included 59 patients with SSc between March 2013 and September 2019. We divided patients into 4 groups: (a) no PH by right heart catheterization (RHC) ( n = 8), (b) no PH by noninvasive screening tests ( n = 16), (c) treatment naïve PAH ( n = 16), and (d) PAH under treatment ( n = 19). Microvascular studies using laser Doppler flowmetry (LDF) were done immediately after RHC or at the time of an outpatient clinic visit (group b). Results: The median (IQR) age was 59 (54–68) years, and 90% were females. The responses to local thermal stimulation and postocclusive reactive hyperemia, acetylcholine, and sodium nitroprusside iontophoresis were similar among groups. The microvascular response to treprostinil was more pronounced in SSc patients without PH by screening tests (% change: 340 (214–781)) compared with SSc‐PAH (naïve + treatment) (Perfusion Units (PU) % change: 153 (94–255) % [ p = .01]). The response to A‐350619 (a soluble guanylate cyclase (sGC) activator) was significantly higher in patients with SSc without PH by screening tests (PU % change: 168 (46–1, 296)) than those with SSc‐PAH (PU % change: 22 (15–57) % [ p = .006]). The % change in PU with A350619 was directly associated with cardiac index and stroke volume index ( R : 0.36, p = .03 and 0.39, p = .02, respectively). Conclusions: Patients with SSc‐PAH have a lower cutaneous microvascular response to a prostacyclin analog treprostinil and the sGC activator A‐350619 when compared with patients with SSc and no evidence of PH on screening tests, presumably due to a peripheral reduction in prostacyclin receptor expression and nitric oxide bioavailability.